THE INFLUENCE OF TEACHER SELF-EFFICACY ON THE QUALITY OF CLASSROOM LEARNING: A SYSTEMATIC LITERATURE REVIEW - Latip, Abdul; Sura Hapsari, Kintania; Kinasih Intani, Tita; Puspitasari Lubis, Try Citra; Angga Saputra, Frasetyo (JURNAL EDUSCIENCE, 2024)
This research aims to analyze and map teacher self-efficacy with two main focuses: mapping teacher self-efficacy indicators and the impact of teacher self-efficacy on learning quality. This research uses a systematic literature review (SLR) with five main stages: protocol search, appraisal, synthesis, analysis, and report. Database searches use publish or perish with selection based on suitability of theme, completeness of journal identity, and year of publication. The results of the article database were analyzed and synthesized to obtain data that was categorized based on themes. The SLR results show that teacher self-efficacy consists of general and specific indicators related to the learning process. Other SLR findings show that teacher self-efficacy has a direct positive influence on student learning outcomes and achievement. Also, self-efficacy positively affects teacher performance, productivity, and discipline in carrying out their duties and roles. The SLR results show that teacher self-efficacy is an essential component that plays a role in improving the quality of teacher performance and learning in the classroom.Keywords: self-efficacy; teachers; learning qualityAbstrakPenelitian ini bertujuan untuk menganalisis dan memetakan efikasi diri guru dengan dua fokus utama, yaitu pemetaan indikator efikasi diri guru dan dampak efikasi diri guru terhadap kualitas pembelajaran. Penelitian ini menggunakan systematic literatur review (SLR) dengan lima tahapan utama, yaitu Protocol search, apprasial, Synthesis, analysis, dan report. Pencarian database menggunakan publish or perish dengan seleksi berdasakan kriteria kesesuaian tema, kelengkapan identitas jurnal, dan tahun publish. Hasil database artikel dianalisis dan disintesis sehingga diperoleh data yang dikategorisasi berdasarkan tema. Hasil SLR menunjukkan bahwa indikator efikasi diri guru terdiri atas indikator efikasi diri yang bersifat umum dan efikasi diri yang berisfat khusus yang spesifik berkaitan dengan proses pembelajaran. Temuan SLR lain menunjukkan bahwa efikasi diri guru memiliki pengaruh positif secara langsung terhadap hasil dan prestasi belajar siswa. Selain itu efikasi diri juga berpengaruh positif terhadap kinerja, produktivitas, dan disiplin guru dalam menjalankan tugas dan perannnya. Hasil SLR tersebut menunjukkan bahwa efikasi diri guru merupakan komponen penting yang berperan dalam peningkatan kualitas kinerja guru dan kualitas pembelajaran di kelasKata Kunci: efikasi diri, guru, kualitas pembelajaran